Self-reported needs after pediatric stroke. (September 2018) - Gordon, Anne L.; Nguyen, Loan; Panton, Anna; Mallick, Andrew A.; Ganesan, Vijeya; Wraige, Elizabeth; McKevitt, Christopher
Abstract: Background: Pediatric stroke has the potential for long term impact on the lives of children and their families. Child-centred intervention depends on understanding of needs from diagnosis onwards. However, little is known about the health and care support self-reported needs of this population. Aims: This study aimed to describe the nature and extent of needs (met and unmet) of pediatric stroke patients and their families and compare these with previously reported adult stroke needs. Methods: The questionnaire, adapted from a previously published adult stroke study, was conducted with parents of children who had an ischemic or haemorrhagic stroke between birth – 18 years, and young people with stroke now aged between 12 and 18 years. Participants were recruited from three tertiary pediatric stroke clinics in England. Levels and type of needs, and self-reported neurological impairment were captured. Comparisons of needs was reported descriptively and explored using Chi-square test. Results: Of 44 participants (39 parents, 5 young people), over two thirds reported at least one unmet need. Over half had difficulties in school-related activities, and over one-third in leisure activities and social relationships. Participants reported similar nature and extent of need when compared to previously reported adult stroke needs. Higher severity of neurological impairment was associated with higher number of needs. Conclusions: Children and young people and their parents have high levels of unmet need across a range of health domains in the months and years after pediatric stroke. This information supports the importance of a needs-based approach to maximising health and well-being. Highlights: Self-reported needs are described across a wide range of domains after child stroke. Most prevalent needs in physical functioning, communication, emotional health, and concentration. Child and adult stroke populations have similar prevalence but differ in domains of unmet need.